Challenge and Obstacles to Promote Sustainable Remanufacturing: A Cross Case Analysis - Mohamed Nasir M.F.; Abdul Rahim A.R.; Zakaria A.F.; Mukhtar A. (Institute of Electrical and Electronics Engineers Inc., 2023)
Life cycle; Quality control; Surveys; Sustainable development; Waste management; Case analysis; Case-studies; Checklist; Cross-case analyse; Industrial processs; Organization management; Original state; Remanufacturing; Sustainable remanufacturing; Used product; Quality management